2012
DOI: 10.2478/10004-1254-63-2012-2186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Mixed Organic Solvents on Blood Pressure in Non-Smoking Women Working in a Pharmaceutical Company

Abstract: Some studies suggest that exposure to industrial solvents can affect blood pressure. The objective of this study was to investigate the effect of a mixture of organic solvents on blood pressure in women working in a pharmaceutical company in Iran. Four hundred and thirty-three women were included in the study. Women working in packing units (group 1) were not exposed to the mixture of organic solvents, women in new laboratory units (group 2) were exposed to the mixture within the permitted range and women work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Several prior studies have observed higher blood pressures among solvent-exposed workers than control groups across a variety of industries, including manufacturing and construction. 4,5,30–33 While not specifically assessed within this study, exposure durations and intensities appear to be important factors with longer durations and higher levels of exposure commensurate with higher systolic blood pressures reported in the literature. 5,30,33 Positive associations of solvent exposures with diastolic blood pressures have also been observed, although this relationship is less consistent than that of systolic blood pressures.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Several prior studies have observed higher blood pressures among solvent-exposed workers than control groups across a variety of industries, including manufacturing and construction. 4,5,30–33 While not specifically assessed within this study, exposure durations and intensities appear to be important factors with longer durations and higher levels of exposure commensurate with higher systolic blood pressures reported in the literature. 5,30,33 Positive associations of solvent exposures with diastolic blood pressures have also been observed, although this relationship is less consistent than that of systolic blood pressures.…”
Section: Discussionmentioning
confidence: 87%
“…1,2 Hispanic/Latino workers, especially those foreign-born, may be especially vulnerable to occupational hazards due to low socioeconomic status and language barriers. 3 Several studies have observed associations between occupational exposures to solvents, 4,5 metals, 68 and pesticides 9,10 with cardiovascular disease risk factors and endpoints. For example, employees at a car manufacturing plant exposed to mixed organic solvents were found to have an increased prevalence of hypertension compared with office workers at the same plant.…”
Section: Introductionmentioning
confidence: 99%
“…Some data indicates that long-term exposure to organic solvents, including gasoline or gasoline compounds, is significantly associated with a higher prevalence of hypertension [14,[143][144][145][146][147]. In particular, Bener et al [144] found a statistically significantly higher prevalence of hypertension among workers exposed to gasoline vapors at different gasoline stations than among unexposed individuals.…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…The pathophysiology of cardiovascular disease associated with gasoline exposure is unclear; however, studies suggest the role of oxidative stress in various pathogenic processes, leading to hypertension and other cardiovascular diseases (Figure 8). These include, but are not limited to, disturbances in the regulatory role of nitric oxide (NO) [146,147,149]. It is known that bioactive gasoline metabolites may induce an oxidant/antioxidant imbalance, generate the ROS, and hence increase oxidative stress.…”
Section: Mechanismsmentioning
confidence: 99%
“…They found an increased arterial hypertension and pathologic changes on ECG of the benzene-exposed subjects in a petrochemical factory (Kotseva and Popov, 1998). The suggested mechanism for benzene to causes hypertension is through disturbing the nitric oxide pathway, however the exact mechanism is still unknown (Wiwanitkit, 2007, Mohammadi et al, 2012.…”
Section: Chronic Exposurementioning
confidence: 99%